Retailer-supplier relationships - Fernie, John (Henry Stewart Talks, 2009)
Evolution of retailer-supplier relationships, International food supply chains, International non food supply chains, Theoretical context, Porter's value chain, Resource based perspective, QR, ECR and CPFR, Future challenges, Ethical issues